Cuidado materno domiciliar às crianças prematuras e/ou de baixo peso nascidas durante a pandemia - Petruccelli, Gabriele (Universidade Federal de São Carlos, 2022)
The study aimed to elucidate the maternal care of preterm and/or low birth weight children at home during the coronavirus pandemic. This is a qualitative study, supported by Symbolic Interactionism, developed in a philanthropic maternity hospital in a city in the interior of São Paulo. Data collection took place from March of September 2021. Ten women, mothers of premature and/or low birth weight children, were interviewed. The Thematic Analysis guided the appreciation of the data. Among the findings, reflections and behaviors were present, in the centrality of care, in order to protect the child from contamination by SARS-CoV-2. The themes “Living with uncertainties during pregnancy, childbirth and birth”, “Social interactions promoting reflections on the chances of contamination”, “Efforts to control the chances of contamination” and “Protection immersed in fears” emerged during the data analysis. It was concluded that the establishment of child care was governed by the fear of contamination by the coronavirus. Thus, it was evident that it is up to the nurse, both in hospital care and in primary care, to support the mother of a child born at risk and to structure their care considering the particularities of the insertion context. Specifically, in the Covid-19 pandemic, the child's susceptibility to infections and a scenario prone to the transmission of the coronavirus, are put in relation.

El estudio tuvo como objetivo dilucidar el cuidado materno de los niños prematuros y/o de bajo peso al nacer en el hogar durante la pandemia de coronavirus. Se trata de un estudio cualitativo, sustentado en el Interaccionismo Simbólico, desarrollado en una maternidad filantrópica de una ciudad del interior de São Paulo. La recolección de datos ocurrió de marzo a septiembre de 2021. Fueron entrevistadas diez mujeres, madres de prematuros y/o de bajo peso al nacer. El Análisis Temático orientó la apreciación de los datos. Entre los hallazgos se hicieron presentes reflexiones y comportamientos, en la centralidad del cuidado, con el fin de proteger al niño de la contaminación por SARS-CoV-2. Los temas “Vivir con incertidumbres durante el embarazo, el parto y el nacimiento”, “Interacciones sociales que promueven reflexiones sobre las posibilidades de contaminación”, “Esfuerzos para controlar las posibilidades de contaminación” y “Protección sumergida en los miedos” surgieron durante el análisis de los datos. Se concluyó que el estabelecimiento de guarderías se rigió por el temor a la contaminación por el coronavirus. Así, se evidenció que corresponde al enfermero, tanto em la atención hospitalaria como en la atención primaria, dar apoyo a la madre del niño nacido em riesgo y estructurar su cuidado considerando las particularidades del contexto de inserción. En concreto, en la pandemia del Covid-19, se pone en relación la susceptibilidad del niño a los contagios y un escenario propenso a la transmisión del coronavirus.
Maternal home care for premature and/or low birth weight children born during the pandemic
Atención materna domiciliaria a los niños prematuros y/o de bajo peso nacidos durante la pandemia
Keywords: Recém-nascido prematuro; Recém-nascido de baixo peso; Enfermagem neonatal; Covid-19; Infant premature; Infant low birth weight; Neonatal nursing; Covid-19; Recién nacido prematuro; Recién nacido de bajo peso; Enfermería neonatal; Covid-19; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PEDIATRICA